Wear-resistant impact-resistant bimetallic composite material and preparation method thereof

By designing a wear-resistant and impact-resistant bimetallic composite structure in metal composite materials, using the finely controlled aluminum alloy matrix layer and multi-layer wear-resistant layer, the problem of insufficient wear resistance and toughness in high-impact environments is solved, and the wear resistance and impact resistance of the material are significantly improved.

CN119876711AInactive Publication Date: 2025-04-25INNER MONGOLIA METAL MATERIAL RES INST
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510163760.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-14
Publication Date
2025-04-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing metal composite materials are difficult to use for a long time in high impact and high wear environments, and have limitations in wear resistance and toughness.

Method used

A wear-resistant and impact-resistant bimetallic composite material is used, which consists of a matrix layer, a transition layer and a wear-resistant layer. The substrate layer includes a base aluminum alloy, a hard phase and a tough phase. Through precise control of components and preparation processes, a high-strength and high-toughness matrix layer is formed. The wear-resistant layer consists of yttrium oxide, zirconia toughened alumina, chromium carbide, nickel, silica and titanium dioxide, and is formed by plasma spraying and laser melting treatment.

Benefits of technology

It significantly improves the wear resistance and impact resistance of the material, extends the service life and reliability under extreme conditions, and is suitable for aerospace, mechanical manufacturing and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 5CZBEJNMYO5MP2VYE8YNHYFH6SKA2EOUI8ZBMN5V
    Figure 5CZBEJNMYO5MP2VYE8YNHYFH6SKA2EOUI8ZBMN5V
  • Figure 9WIEW3YOEMCFTSNXGXPEOSDVJFNC62LU4X5FLIPO
    Figure 9WIEW3YOEMCFTSNXGXPEOSDVJFNC62LU4X5FLIPO
  • Figure AN5SQ1W2WCMVCMQVTNDSLH3QXGBGYQADGMQKNBRR
    Figure AN5SQ1W2WCMVCMQVTNDSLH3QXGBGYQADGMQKNBRR
Patent Text Reader

Abstract

The invention discloses a wear-resistant and impact-resistant bimetallic composite material and a preparation method thereof, and relates to the technical field of composite materials. The wear-resistant and impact-resistant bimetallic composite material comprises a matrix layer, a transition layer and a wear-resistant layer, the matrix layer comprises a basic aluminum alloy, a hard phase and a tough phase, the transition layer is a nickel plasma spraying layer, and the wear-resistant layer is composed of yttrium oxide, zirconium oxide toughened aluminum oxide, chromium carbide, nickel, silicon dioxide and titanium dioxide. Raw materials of the base body layer are mixed and smelted, a crude base body is obtained, homogenization treatment, extrusion forming and heat treatment are conducted, and the base body layer is obtained; and the surface of the base body layer is polished and cleaned, the transition layer is prepared on the surface of the base body layer through plasma spraying treatment after preheating is conducted, laser melting treatment is conducted on the transition layer, and the wear-resistant and impact-resistant bimetallic composite material is prepared. The wear-resistant and impact-resistant bimetallic composite material prepared by the invention has excellent mechanical properties, wear resistance and impact resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite materials, in particular to a wear-resistant and impact-resistant bimetallic composite material and a preparation method thereof. Background Art

[0002] With the continuous development of industrial technology, the performance requirements for materials are getting higher and higher, especially in terms of wear resistance and impact resistance. Traditional materials often cannot meet the application requirements of high strength and high wear resistance. Therefore, the development of new composite materials has become one of the hot spots in material science research. Metal composite materials are widely used in aerospace, automobile, mining machinery and other fields due to their excellent mechanical properties and wear resistance.

[0003] Existing metal composite materials have certain limitations in wear resistance and toughness, and are difficult to use for a long time in high-impact and high-wear environments. Therefore, a new type of wear-resistant and impact-resistant bimetallic composite material is urgently needed to improve its service life and reliability under extreme conditions. Summary of the invention

[0004] The purpose of the present invention is to provide a wear-resistant and impact-resistant bimetallic composite material and a preparation method thereof, so as to solve the problems raised in the background technology.

[0005] In a first aspect, the present invention provides a wear-resistant and impact-resistant bimetallic composite material, comprising a base layer, a transition layer and a wear-resistant layer, wherein the base layer comprises the following components in parts by weight: A. 77.6-97 parts of basic aluminum alloy; The mass fractions of the components in the basic aluminum alloy are as follows: Al: 82-89 parts, Zn: 7-12 parts, Mg: 2-3 parts, Cu: 2-3 parts; B. Hard phase 0.96-1.2 parts; The weight proportions of the components in the hard phase are as follows: Ti: 8.9-27 parts, Zr: 6.4-21.5 parts, Cr: 19.3-32.1 parts, W: 0.9-7.2 parts, Mo: 1.5-12.2 parts; C. Tough phase 1.44-1.8 parts; The weight proportions of the components in the hard phase are as follows: Ni: 93.1-94.4 parts, Fe: 5.6-6.9 parts.

[0006] Furthermore, the wear-resistant layer is composed of yttrium oxide, zirconium oxide toughened aluminum oxide, chromium carbide, nickel, silicon dioxide and titanium dioxide.

[0007] Furthermore, the molar ratio of zirconium oxide to aluminum oxide in the zirconium oxide toughened aluminum oxide is 4:6.

[0008] Furthermore, the mass ratio of yttrium oxide, zirconium oxide toughened aluminum oxide, chromium carbide, nickel, silicon dioxide and titanium dioxide in the wear-resistant layer is (0.9-1.2):(75-100):(50-66.7):(50-66.7):(0.75-1):(1-1.2).

[0009] In a second aspect, the present invention further provides a method for preparing the above-mentioned wear-resistant and impact-resistant bimetallic composite material, comprising the following steps: S1. Mix and melt the base aluminum alloy, the hard phase and the tough phase to obtain a crude matrix, set a heating program, homogenize the crude matrix for 6-9 hours, extrude and form, set a cooling program, heat treat the crude matrix for 10-14 hours, and obtain a matrix layer; S2. The surface of the substrate layer is polished with 80-120 mesh coarse sandpaper, then with 180-240 mesh fine sandpaper, and finally with 320-400 mesh polishing sandpaper, ultrasonically cleaned, preheated at 150℃-200℃ for 5-60min, firstly prepared a transition layer on the surface of the substrate layer by plasma spraying, and then yttrium oxide, zirconium oxide toughened alumina, chromium carbide, nickel, silicon dioxide and titanium dioxide are ground until mixed evenly, laser melting treatment is performed on the transition layer to obtain a wear-resistant layer, and cooled to room temperature to obtain a wear-resistant and impact-resistant bimetallic composite material.

[0010] Further, in S1, the temperature rising program is as follows: initially at 400°C-440°C for 2-3 hours, heating to 500°C-530°C at a heating rate of 2-3°C / min, and keeping for 4-6 hours.

[0011] Further, in S1, the cooling procedure is as follows: initially keep at 300°C-320°C for 4-6h, cool to 175°C-190°C at a cooling rate of 1-1.5°C / min, keep for 6-8h, and air cool to room temperature.

[0012] It should be noted that through precisely controlled heating and cooling procedures, including homogenization treatment and heat treatment, component segregation can be eliminated, grain size can be refined, and the precipitation strengthening effect of the alloy can be fully exerted.

[0013] Furthermore, in S2, the spraying powder used in the plasma spraying process is nickel.

[0014] Furthermore, in S2, the process parameters of the plasma spraying treatment are as follows: the current is 420A and the voltage is 44V.

[0015] It should be noted that the use of nickel as the transition layer can effectively improve the overall bonding strength by utilizing nickel's good ductility and bonding ability with the base layer and the wear-resistant layer. Plasma spraying can obtain a uniform and dense transition layer and form a good mechanical bond with the base layer.

[0016] Further, in S2, the process parameters of the laser melting treatment are as follows: argon gas protects the laser pool, the gas flow rate is 9-12 L / min, the laser power is 1.7-2.1 kW, the spot diameter is 3-3.5 mm, and the scanning speed is 8-10 mm / s.

[0017] It should be noted that argon protection can prevent high-temperature oxidation and ensure the quality of the wear-resistant layer. Laser melting treatment can form a metallurgical bond between the wear-resistant layer material and the transition layer, significantly improve the bonding strength, ensure the quality and uniformity of the wear-resistant layer, and obtain better interface performance.

[0018] Compared with the prior art, the present invention has the following beneficial effects: 1. By controlling the contents of Cr, Mn, V, W, and Al, a good foundation for the mechanical properties of the aluminum alloy matrix is ​​laid; by controlling the contents of Y, Si, Zr, Ti, and Li, a good deoxidation effect and grain refinement effect are achieved, intergranular corrosion is effectively avoided, the cracking sensitivity of the aluminum alloy matrix is ​​reduced, and the performance of the aluminum alloy matrix is ​​improved; Zr and Li generate strengthening phases Al3Zr and Al2CuLi to improve the strength and toughness of the aluminum alloy matrix; Y, Si and Fe cooperate to improve the fatigue resistance of the aluminum alloy matrix; by controlling the contents of Al, Cu, Mg, and Zn, dispersed strengthening phases Al2Cu, Al2CuMg, and MgZn2 are formed, and the strengthening phases work synergistically to refine the cast grains, increase the dislocation density and recrystallization temperature of the aluminum alloy matrix, inhibit recrystallization, and improve the tensile strength, yield strength, hardness, toughness and other mechanical properties of the aluminum alloy matrix.

[0019] 2. During the homogenization treatment process, the homogenization treatment time is set within different temperature ranges to improve the size and distribution of the strengthening phase precipitation, improve the strength, hardness, toughness, corrosion resistance and processing performance of the aluminum alloy, reduce deformation resistance, avoid non-equilibrium solidification resulting in uneven raw materials and non-equilibrium solidification structure effects resulting in non-equilibrium structure and coarse precipitation phases; adopt a gradual cooling method to control the temperature and holding time to refine the primary aluminum alloy structure, prevent recrystallization behavior, prevent cracking of the extruded aluminum alloy matrix, and further enhance the strength, toughness and corrosion resistance of the aluminum alloy profile.

[0020] 3. During the plasma cladding process, nano ceramic powder has a large specific surface area and high energy absorption utilization rate. By reasonably setting various parameters of plasma cladding, SiO2 and Cr3C2 are partially decomposed at high temperature, and C and Al generate fine needle-shaped dendrites Al4C3. Si and Cr are dissolved in the aluminum alloy matrix, which improves the hardness of the ceramic coating and the bonding strength with the aluminum alloy matrix; Cr2O3, NiO, and Al2O3 are dispersed between the fine subgrains on the surface of the molten aluminum alloy, and together form a cellular dendrite structure. In addition, nano-scale Cr2O3 and Al2O3 also play the role of dispersion strengthening and fine grain strengthening on the surface of the aluminum alloy, improving the organizational structure of the cladding layer, so that it has good strength, hardness and impact resistance.

[0021] In summary, the present invention provides a wear-resistant and impact-resistant bimetallic composite material and a preparation method thereof. The composite material consists of a substrate layer, a transition layer and a wear-resistant layer. By finely controlling the composition and preparation process of the substrate layer and the wear-resistant layer materials, the strength, toughness, corrosion resistance, fatigue resistance and other mechanical properties of the aluminum alloy substrate are improved, the hardness of the ceramic coating and the bonding strength with the aluminum alloy substrate are enhanced, and the organizational structure of the cladding layer is improved, so that it has good strength, hardness and impact resistance. The composite material can be applied to aerospace, machinery manufacturing, petrochemical and other fields, and has broad application prospects. DETAILED DESCRIPTION

[0022] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] A wear-resistant and impact-resistant bimetallic composite material, comprising a base layer, a transition layer and a wear-resistant layer; The matrix layer includes 97 parts of the base aluminum alloy, 1.2 parts of the hard phase and 1.8 parts of the ductile phase; The weight proportions of each component in the basic aluminum alloy are as follows: Al: 89 parts, Zn: 12 parts, Mg: 3 parts, Cu: 3 parts; the weight proportions of each component in the hard phase are as follows: Ti: 8.9 parts, Zr: 6.4 parts, Cr: 19.3 parts, W: 0.9 parts, Mo: 1.5 parts: The weight proportions of each component in the hard phase are as follows: Ni: 93.1 parts, Fe: 5.6 parts.

[0024] The transition layer is a nickel plasma sprayed layer.

[0025] The wear-resistant layer is composed of yttrium oxide, zirconium oxide toughened alumina, chromium carbide, nickel, silicon dioxide and titanium dioxide in a mass ratio of 1.2:100:67:67:1:1.2, wherein the molar ratio of zirconium oxide to aluminum oxide in the zirconium oxide toughened alumina is 4:6.

[0026] Embodiment 1: A method for preparing a wear-resistant and impact-resistant bimetallic composite material comprises the following steps: S1. Mix and melt the base aluminum alloy, the hard phase and the tough phase to obtain a crude matrix, heat it at 440°C for 3 hours, heat it to 530°C at a heating rate of 2°C / min, heat it for 6 hours, extrude it, heat it at 300°C-320°C for 6 hours, cool it to 180°C at a cooling rate of 18°C / min, heat it for 8 hours, and air-cool it to room temperature to obtain a matrix layer; S2. The surface of the substrate layer is polished and cleaned, and preheated at 200°C for 30 minutes. A transition layer is first prepared on the surface of the substrate layer by plasma spraying. The spraying powder used is nickel, the current is 420A, and the voltage is 44V. Yttrium oxide, zirconium oxide toughened alumina, chromium carbide, nickel, silicon dioxide and titanium dioxide are ground until they are evenly mixed. Laser melting is performed on the transition layer using a TruFiber 3000 series fiber laser and an argon-protected laser pool. The gas flow rate is 10L / min, the laser power is 2.1kW, the spot diameter is 3.2mm, and the scanning speed is 8mm / s to obtain a wear-resistant layer. The layer is cooled to room temperature to obtain a wear-resistant and impact-resistant bimetallic composite material.

[0027] Embodiment 2: A method for preparing a wear-resistant and impact-resistant bimetallic composite material comprises the following steps: S1. Mix and melt the base aluminum alloy, the hard phase and the tough phase to obtain a crude matrix, heat it at 400°C for 2 hours, heat it to 510°C at a heating rate of 3°C / min, heat it for 6 hours, extrude it, heat it at 310°C for 6 hours, cool it to 190°C at a cooling rate of 1.5°C / min, heat it for 7 hours, and air-cool it to room temperature to obtain a matrix layer; S2. The surface of the substrate layer is polished and cleaned, and preheated at 200°C for 30 minutes. A transition layer is first prepared on the surface of the substrate layer by plasma spraying. The spraying powder used is nickel, the current is 420A, and the voltage is 44V. Yttrium oxide, zirconium oxide toughened alumina, chromium carbide, nickel, silicon dioxide and titanium dioxide are ground until they are evenly mixed. Laser melting is performed on the transition layer using a TruFiber 3000 series fiber laser and an argon-protected laser pool. The gas flow rate is 10L / min, the laser power is 2.1kW, the spot diameter is 3.2mm, and the scanning speed is 8mm / s to obtain a wear-resistant layer. The layer is cooled to room temperature to obtain a wear-resistant and impact-resistant bimetallic composite material.

[0028] Embodiment 3: A method for preparing a wear-resistant and impact-resistant bimetallic composite material comprises the following steps: S1. Mix and melt the base aluminum alloy, the hard phase and the tough phase to obtain a crude matrix, keep the temperature at 410°C for 2 hours, heat it to 520°C at a heating rate of 2.5°C / min, keep it for 6 hours, extrude it, keep it at 305°C for 4 hours, cool it to 175°C at a cooling rate of 1°C / min, keep it for 6 hours, and air-cool it to room temperature to obtain a matrix layer; S2. The surface of the substrate layer is polished and cleaned, and preheated at 200°C for 30 minutes. A transition layer is first prepared on the surface of the substrate layer by plasma spraying. The spraying powder used is nickel, the current is 420A, and the voltage is 44V. Yttrium oxide, zirconium oxide toughened alumina, chromium carbide, nickel, silicon dioxide and titanium dioxide are ground until they are evenly mixed. Laser melting is performed on the transition layer using a TruFiber 3000 series fiber laser and an argon-protected laser pool. The gas flow rate is 10L / min, the laser power is 2.1kW, the spot diameter is 3.2mm, and the scanning speed is 8mm / s to obtain a wear-resistant layer. The layer is cooled to room temperature to obtain a wear-resistant and impact-resistant bimetallic composite material.

[0029] Embodiment 4: A method for preparing a wear-resistant and impact-resistant bimetallic composite material comprises the following steps: S1. Mix and melt the base aluminum alloy, the hard phase and the tough phase to obtain a crude matrix, heat it at 430°C for 3 hours, heat it to 530°C at a heating rate of 3°C / min, heat it for 5 hours, extrude it, heat it at 320°C for 6 hours, cool it to 175°C at a cooling rate of 1.5°C / min, heat it for 8 hours, and air-cool it to room temperature to obtain a matrix layer; S2. The surface of the substrate layer is polished and cleaned, and preheated at 200°C for 30 minutes. A transition layer is first prepared on the surface of the substrate layer by plasma spraying. The spraying powder used is nickel, the current is 420A, and the voltage is 44V. Yttrium oxide, zirconium oxide toughened alumina, chromium carbide, nickel, silicon dioxide and titanium dioxide are ground until they are evenly mixed. Laser melting is performed on the transition layer using a TruFiber 3000 series fiber laser and an argon-protected laser pool. The gas flow rate is 10L / min, the laser power is 2.1kW, the spot diameter is 3.2mm, and the scanning speed is 8mm / s to obtain a wear-resistant layer. The layer is cooled to room temperature to obtain a wear-resistant and impact-resistant bimetallic composite material.

[0030] Embodiment 5: A method for preparing a wear-resistant and impact-resistant bimetallic composite material comprises the following steps: S1. Mix and smelt the base aluminum alloy, the hard phase and the tough phase to obtain a crude matrix, heat it at 400°C for 2 hours, heat it to 500°C at a heating rate of 2°C / min, heat it for 4 hours, extrude it, heat it at 300°C for 4 hours, cool it to 185°C at a cooling rate of 1°C / min, heat it for 6 hours, and air-cool it to room temperature to obtain a matrix layer; S2. The surface of the substrate layer is polished and cleaned, and preheated at 200°C for 30 minutes. A transition layer is first prepared on the surface of the substrate layer by plasma spraying. The spraying powder used is nickel, the current is 420A, and the voltage is 44V. Yttrium oxide, zirconium oxide toughened alumina, chromium carbide, nickel, silicon dioxide and titanium dioxide are ground until they are evenly mixed. Laser melting is performed on the transition layer using a TruFiber 3000 series fiber laser and an argon-protected laser pool. The gas flow rate is 10L / min, the laser power is 2.1kW, the spot diameter is 3.2mm, and the scanning speed is 8mm / s to obtain a wear-resistant layer. The layer is cooled to room temperature to obtain a wear-resistant and impact-resistant bimetallic composite material.

[0031] test: 1. Hardness test The wear-resistant and impact-resistant bimetallic composite materials prepared in Examples 1-5 were subjected to a microhardness test using a HVS-1000A microhardness tester with an applied load of 50 g and a holding time of 15 s.

[0032] The test results are shown in Table 1.

[0033] 2. Impact test The wear-resistant and impact-resistant bimetallic composite materials prepared in Examples 1-5 were subjected to a pendulum impact test in accordance with GB / T229-2007 “Charpy Pendulum Impact Test Method for Metallic Materials”.

[0034] The test results are shown in Table 2.

[0035] 3. Wear test The wear-resistant and impact-resistant bimetallic composite materials prepared in Examples 1-5 were subjected to sliding friction and wear tests, and the test conditions were: a constant speed of 400 rpm and a constant load of 7N.

[0036] The test results are shown in Table 3.

[0037] 4. Tensile test The wear-resistant and impact-resistant bimetallic composite materials prepared in Examples 1-5 were subjected to a microhardness test pendulum impact test in accordance with ASTM E8 / E8M-21: Standard Methods for Tensile Testing of Metallic Materials.

[0038] The test results are shown in Table 4.

[0039] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0040] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A wear-resistant and impact-resistant bimetallic composite material, characterized in that: It includes a base layer, a transition layer and a wear-resistant layer: the base layer includes the following components in parts by weight: A. 77.6-97 parts of basic aluminum alloy; The mass fractions of the components in the basic aluminum alloy are as follows: Al: 82-89 parts, Zn: 7-12 parts, Mg: 2-3 parts, Cu: 2-3 parts; B. Hard phase 0.96-1.2 parts; The weight proportions of the components in the hard phase are as follows: Ti: 8.9-27 parts, Zr: 6.4-21.5 parts, Cr: 19.3-32.1 parts, W: 0.9-7.2 parts, Mo: 1.5-12.2 parts; C. Tough phase 1.44-1.8 parts; The weight proportions of the components in the tough phase are as follows: Ni: 93.1-94.4 parts, Fe: 5.6-6.9 parts; The wear-resistant layer is composed of yttrium oxide, zirconium oxide toughened aluminum oxide, chromium carbide, nickel, silicon dioxide and titanium dioxide.

2. The method for preparing a wear-resistant and impact-resistant bimetallic composite material according to claim 1, characterized in that: The molar ratio of zirconium oxide to aluminum oxide in the zirconium oxide toughened aluminum oxide is 4:

6.

3. The method for preparing a wear-resistant and impact-resistant bimetallic composite material according to claim 1, characterized in that: The mass ratios of yttria, zirconium oxide toughened aluminum oxide, chromium carbide, nickel, silicon dioxide and titanium dioxide in the wear-resistant layer are (0.9-1.2):(75-100):(50-66.7):(50-66.7):(0.75-1):(1-1.2).

4. A method for preparing the wear-resistant and impact-resistant bimetallic composite material according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1. Mix and melt the base aluminum alloy, the hard phase and the tough phase to obtain a crude matrix, set a heating program, homogenize the crude matrix for 6-9 hours, extrude and form, set a cooling program, heat treat the crude matrix for 10-14 hours, and obtain a matrix layer; S2. Grind and clean the surface of the substrate layer, preheat at 150℃-200℃ for 5-60min, first use plasma spraying to prepare a transition layer on the surface of the substrate layer, then grind yttrium oxide, zirconium oxide toughened alumina, chromium carbide, nickel, silicon dioxide and titanium dioxide until they are evenly mixed, perform laser melting on the transition layer to obtain a wear-resistant layer, cool to room temperature, and obtain a wear-resistant and impact-resistant bimetallic composite material.

5. The method for preparing a wear-resistant and impact-resistant bimetallic composite material according to claim 4, characterized in that: In S1, the heating program is as follows: initially at 400°C-440°C for 2-3 h, then heated to 500°C-530°C at a heating rate of 2-3°C / min, and kept for 4-6 h.

6. The method for preparing a wear-resistant and impact-resistant bimetallic composite material according to claim 4, characterized in that: In S1, the cooling program is as follows: initially keep at 300℃-320℃ for 4-6h, cool to 175℃-190℃ at a cooling rate of 1-1.5℃ / min, keep for 6-8h, and air cool to room temperature.

7. The method for preparing a wear-resistant and impact-resistant bimetallic composite material according to claim 4, characterized in that: In S2, the spraying powder used in the plasma spraying process is nickel.

8. The method for preparing a wear-resistant and impact-resistant bimetallic composite material according to claim 4, characterized in that: In S2, the process parameters of the plasma spraying treatment are as follows: the current is 420A and the voltage is 44V.

9. The method for preparing a wear-resistant and impact-resistant bimetallic composite material according to claim 4, characterized in that: In S2, the process parameters of the laser melting treatment are as follows: argon gas protects the laser pool, the gas flow rate is 9-12 L / min, the laser power is 1.7-2.1 kW, the spot diameter is 3-3.5 mm, and the scanning speed is 8-10 mm / s.

Citation Information

Patent Citations

  • Laser fusion welding method of abrasion-proof heat-proof composite coating on surface of tuyeres of blast furnace port sleeve

    CN101109026A

  • Preparation method of aluminum alloy wear-resistant coating

    CN103103469A

  • Copper-based anti-abrasion anti-impact bi-metal composite material and preparation method thereof

    CN105665695A

  • High-strength corrosion-resistant aluminum alloy profile and preparation method thereof

    CN106399762A

  • High-strength wear-resisting aluminum alloy profile applied to high-speed railway and preparation method of high-strength wear-resisting aluminum alloy profile

    CN108130465A